2002
DOI: 10.1038/sj.ijo.0801970
|View full text |Cite
|
Sign up to set email alerts
|

Markers of chronic inflammation and obesity: a prospective study on the reversibility of this association in middle-aged women undergoing weight loss by surgical intervention

Abstract: BACKGROUND: Human adipose tissue expresses and releases proinflammatory cytokines and these measures of chronic inflammation have recently been associated with obesity. HYPOTHESIS: To test whether the proinflammatory state is reversible in subjects undergoing weight loss by surgical measures. SUBJECTS AND METHODS: Twenty morbidly obese women participated in this prospective study. Subjects were examined for fat mass, high-sensitive C-reactive protein (hs-CRP), interleukin 6 (IL-6) and tumor necrosis factor-alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 26 publications
(18 reference statements)
7
123
3
1
Order By: Relevance
“…16,36 CRP is positively associated with BMI and we and others have shown that energy striction and weight loss lowers CRP. 16,37,38 Ziccardi et al 7 found reductions in IL-6, VCAM-1 and ICAM-1 following weight loss of 10 kg however we demonstrated reductions in the ICAM-1 but not VCAM or IL-6. The reason for these differences is not clear although other studies with much greater weight loss have shown no change in IL-6, 38 whereas Nicoletti et al 9 and Esposito et al 39 observed reduction in IL-6 after weight loss.…”
Section: Discussioncontrasting
confidence: 53%
“…16,36 CRP is positively associated with BMI and we and others have shown that energy striction and weight loss lowers CRP. 16,37,38 Ziccardi et al 7 found reductions in IL-6, VCAM-1 and ICAM-1 following weight loss of 10 kg however we demonstrated reductions in the ICAM-1 but not VCAM or IL-6. The reason for these differences is not clear although other studies with much greater weight loss have shown no change in IL-6, 38 whereas Nicoletti et al 9 and Esposito et al 39 observed reduction in IL-6 after weight loss.…”
Section: Discussioncontrasting
confidence: 53%
“…38,39,[52][53][54][55] The adipokines adiponectin and leptin have previously been connected with pro-inflammatory markers. A reduction in FM has been shown to induce a decline in leptin concentration 28,35,40,41 and a rise in adiponectin concentration. 14,15,29,40 However, the present study failed to provide the expected increase in adiponectin as a response to the fat loss possibly due to the study being simply underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…16,28,29,35,36 However, only hs-CRP and IL-6 were Figure 2 Loading plot of factor structure of the pro-inflammatory markers high-sensitive C-reactive protein (hs-CRP), interleukin-6 (IL-6), fibrinogen, haptoglobin, transferrin and the adipokines leptin and adiponectin. Factor 1 was related to fibrinogen (0.81), CRP (0.63), haptoglobin (0.71), IL-6 (0.64) whereas adiponectin, leptin and transferrin were not.…”
Section: Discussionmentioning
confidence: 99%
“…Here, again, polymorphisms in immune genes modulate risk, implying a pathogenetic significance for immune gene products Table 4 Interventions that have an impact on the inflammatory state Inflammatory mediators whose concentrations are reduced by weight loss and/or physical exercise [190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207] CRP, TNF-α, soluble TNF-α receptor 2, IL-6, IL-18, MCP-1, PAI-1, t-PA, soluble ICAM-1, soluble VCAM-1, P-selectin Inflammatory mediators whose concentrations are reduced by glucose-lowering drugs [186,188,[208][209][210][211][212][213][214][215][216][217] Sulphonylurea: TNF-α Metformin: CRP Glitazones: CRP, SAA, TNF-α, soluble CD40 ligand, PAI-1 Insulin: CRP, IL-1, IL-6, TNF-α, soluble ICAM-1, MCP-1, PAI-1 SAA Serum amyloid A, t-PA tissue plasminogen activator, VCAM-1 vascular cell adhesion molecule-1 [171][172][173]. Where studied, the upregulation of inflammatory mediators was linked to increased oxidative stress, impaired mitochondrial function and abnormal cholesterol metabolism [174][175][176].…”
Section: Low-grade Inflammation and Healthmentioning
confidence: 99%